MINERAL ANALYSIS OF AVERRHOA BILIMBI L. – A POTENTIAL FRUIT - BHAURAV.T.DANGAT; ANUJA A. SHINDE; DIPALI N. JAGTAP; VARSHARANI R. DESAI; Shinde, Prachi B.; RAJARAM.V.GURAV (Asian Journal of Pharmaceutical and Clinical Research, 2014)
Averrhoa bilimbi L. (Oxalidaceae) is widely distributed and cultivated throughout tropical countries for their fruits. Parts such as leaves, bark, fruits are widely used in medicine as a folk remedy for many symptoms. This study provides morphological and biochemical characteristics of half-ripen bilimbi fruits. During present study physical and chemical properties of Bilimbi fruits were studied at half-ripen stage for potential benefits based on its mineral content. Phosphorus content of the fruits was higher at half-ripen stage i.e. 39 ± 1.7%, while in case of minor elements, Molybdenum is present in least amount i.e. 0.04 ± 0.05 ppm. This Chemical studies reveals; these fruits are good source of minerals such as Potassium, Phosphorus, Nitrogen, Calcium, Magnesium and Iron suggesting its use as a potential fruit. Keywords: Averrhoa, Bilimbi, Mineral analysis, Oxalidaceae.